Modeling and Simulation for Performance Evaluation of Optical Quantum Channels in Quantum key Distribution Systems - Mushatet, Adil Fadhil; Tawfeeq, Shelan Khasro (Al-Khwarizmi Engineering Journal, 2021)
In this research work, a simulator with time-domain visualizers and configurable parameters using a continuous time simulation approach with Matlab R2019a is presented for modeling and investigating the performance of optical fiber and free-space quantum channels as a part of a generic quantum key distribution system simulator. The modeled optical fiber quantum channel is characterized with a maximum allowable distance of 150 km with 0.2 dB/km at =1550nm. While, at =900nm and =830nm the attenuation values are 2 dB/km and 3 dB/km respectively. The modeled free space quantum channel is characterized at 0.1 dB/km at =860 nm with maximum allowable distance of 150 km also. The simulator was investigated in terms of the execution of the BB84 protocol based on polarizing encoding with consideration of the optical fiber and free-space quantum channel imperfections and losses by estimating the quantum bit error rate and final secure key. This work shows a general repeatable modeling process for significant performance evaluation. The most remarkable result that emerged from the simulated data generated and detected is that the modeling process provides guidance for optical quantum channels design and characterization for other quantum key distribution protocols.